The Effect Of Puppets as Teaching Media on the Speaking Competency - Wedana, I Made Lanang; Suarnajaya, Wayan; Adnyani, Luh Diah Surya (Universitas Pendidikan Ganesha, 2019)
This study focused on investigating the effect of puppets as a teaching media on students’ speaking competency. It was an experimental research administering post-test only control group design. The population was the eighth-grade students of SMP N 6 Singaraja. The samples were VIII B1 class as experimental group and VIII B3 as a control group. The experimental group was treated by using puppets as teaching media, whereas the control group was treated by using the conventional technique. The instruments used in this study to collect the data were the teaching scenario and post-test in the form of a speaking test. The data were then analyzed descriptively, inferentially and effect size. The result was significant. It can be seen from both group's mean score where the experimental group’s score was 93.84 while control group’s score was 90.22 the value of tob (t observed) was 2.111 and it was higher than tcv (t critical value) that was 1.669 (a=0.5). It indicates that there is a significant effect on students’ speaking competency who were taught by puppet and those who were taught by conventional technique.